2018
DOI: 10.1016/j.appet.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the association between inhibitory control and loss of control over eating among adolescents

Abstract: Evidence was found for problems with overall self-regulation in adolescents with loss of control over eating. Concerning the specific role of inhibitory control, future studies should replicate whether automatic processing is indeed a crucial moderator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 67 publications
0
22
1
Order By: Relevance
“…It also contradicts previous empirical evidence for this dual-pathway perspective in the context of overweight or unhealthy eating in children (e.g., Kemps et al, 2020), adolescents (e.g., Stok et al, 2015), and adults (e.g., Kakoschke et al, 2015). Nevertheless, the current result is in line with other previous observations in adults (Manasse et al, 2015) as well as in adolescents (Van Malderen et al, 2018) which have also found an interaction between poor inhibitory control and low attentional bias. However, it should be noted that all these previous studies focused on overweight or unhealthy eating as the outcome variable and not food choice specifically.…”
Section: Discussioncontrasting
confidence: 66%
“…It also contradicts previous empirical evidence for this dual-pathway perspective in the context of overweight or unhealthy eating in children (e.g., Kemps et al, 2020), adolescents (e.g., Stok et al, 2015), and adults (e.g., Kakoschke et al, 2015). Nevertheless, the current result is in line with other previous observations in adults (Manasse et al, 2015) as well as in adolescents (Van Malderen et al, 2018) which have also found an interaction between poor inhibitory control and low attentional bias. However, it should be noted that all these previous studies focused on overweight or unhealthy eating as the outcome variable and not food choice specifically.…”
Section: Discussioncontrasting
confidence: 66%
“…Poorer inhibitory control has been generally linked to LOC and binge eating in several cross-sectional studies of adults and youth (Kittel et al, 2017;Manasse et al, 2015;Manasse et al, 2016;Van Malderen et al, 2018). In the current study, we demonstrated for the first time that such deficits also have direct relevance to the severity of LOC eating in real-time, particularly in the context of greater negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the PFC in addiction underlies not only compulsive drug taking but also accounts for the disadvantageous behaviors that are associated with addiction and the erosion of free will (53). The role of inhibitory control in relation to the development and maintenance of loss of control over behavior is still to be fully elucidated, as well as the role of automatic processes as potential mediating factors (54). Herein, we focused on the symptom cluster "loss of control" (i.e., unsuccessful efforts to control, cut back, or stop gambling), which appears to be mainly related to impaired reward-related decision-making and deficits in executive functions.…”
Section: Response Inhibitionmentioning
confidence: 99%